Radial liquid crystal alignment based on circular rubbing of a substrate coated with poly(N-vinyl carbazole) film - Chen, Yuan-Di; Fuh, Andy Ying-Guey; Liu, Cheng-Kai; Cheng, Ko-Ting (Journal of physics. D, Applied physics, 2011)
This paper presents a simple method to produce radial liquid crystal (LC) alignment layers using circular rubbing of poly( N -vinyl carbazole) (PVK) films. The produced layer can be used for fabricating axially symmetric homogeneous–radial, homeotropic–radial and radial–radial LC alignment devices by combining a rubbed PVK-coated substrate with another one with a desired LC alignment layer. The transmittance–voltage curves of the fabricated LC devices at various positions are measured to examine the uniformity of the alignment effect. Additionally, the PVK film does not absorb visible light, and can be operated at high temperatures.